The Effect of Measurement Errors on Parameter Estimates and Forecasts: A Case Study Based on the Canadian Preliminary National Accounts - Denton, Frank T.; Kuiper, John (The Review of Economics and Statistics, 1965)
Frank T. Denton, John Kuiper, The Effect of Measurement Errors on Parameter Estimates and Forecasts: A Case Study Based on the Canadian Preliminary National Accounts, The Review of Economics and Statistics, Vol. 47, No. 2 (May, 1965), pp. 198-206